ANALISIS FILM UP - Gunawan, I Putu Rezza Sastra (Pusat Penerbitan LPPM ISI Bali, 2025)
The film UP (2009), the work of Pixar Animation Studios and Walt Disney Pictures, is an animated film that excels in conveying stories through visual beauty and character design. This film depicts the emotional journey of Carl Fredricksen, a stubborn old man, and Russell, a passionate Boy Scout, on an extraordinary adventure to Paradise Falls. By utilizing a strong visual aesthetic and deep symbolism, UP manages to create a strong emotional connection with audiences of all ages. Carl's character design's rigid shapes and sharp angles reflect his tough and tough personality due to loss, while Russell's round, expressive form conveys his energy and innocence as a child.